Bioequivalence study of a fixed dose combination tablet containing rabeprazole and diclofenac sodium in healthy Indian subjects - Mukherjee, Jayanti; Das, Ayan; Chakrabarty, Uday S.; Sahoo, Bijay; Sengupta, Pinaki; Chatterjee, Bappaditya; Roy, Bikash; Pal, Tapan K. (Arzneimittelforschung, 2010)
The pharmacokinetics of rabeprazole (CAS 117976-89-3) and diclofenac sodium (CAS 15307-79-6) has been extensively evaluated in adult human volunteers individually after oral administration of tablet formulation. However, no published data is available regarding the combined pharmacokinetics and bioavailability of this particular fixed dose combination. In light of the above, a clinical study was designed to evaluate the bioequivalence of two fixed dose combination (FDC) products (reference and test) of two manufacturers containing rabeprazole 20 mg and diclofenac sodium 100 mg slow release (SR) tablet in healthy Indian male volunteers.Each subject received a test FDC and a reference FDC in a randomized, single dose, fasting state, two period, and crossover study design with a one-week washout period between the doses. Extraction of the drugs from the plasma was carried out by the precipitation method. Analysis of rabeprazole and diclofenac sodium from plasma samples was done by a simple and sensitive HPLC method using a UV detector. An analysis of variance was performed on the pharmacokinetic parameters of Cmax, tmax, AUC0–t, and AUC0–∞ using general linear model (GLM) procedures in which sources of variation were subject, formulation and period.The results of this study indicated that there were no statistically significant differences between the logarithmically transformed AUC0–∞ and Cmax values of the two preparations. The 90% confidence interval for the ratio of logarithmically transformed AUC0–t, AUC0–∞ and Cmax were within the bioequivalence limit of 0.80–1.25 and the relative bioavailability of rabeprazole and diclofenac sodium were found to be 98.6% and 98.9% respectively in the test product. Thus, these findings clearly indicated that the two products are bioequivalent in terms of rate and extent of drug absorption.
Keywords: Analgesics; Anti-inflammatories; CAS 15307-79-6; CAS 117976-89-3; Diclofenac sodium; Proton pump inhibitors; Rabeprazole